Relationship between cerebrospinal fluid circulation markers, brain degeneration, and cognitive impairment in cerebral amyloid angiopathy - Li Zhao; Lingyun Liu; Miao Lin; Linyun Xie; Hui Hong; Qingze Zeng; Shuyue Wang; Ruiting Zhang; Zhenhua Zhao; Zhenhua Zhao; Peiyu Huang; on behalf of the Alzheimer’s Disease Neuroimaging Initiative (Frontiers in Aging Neuroscience)
ObjectivesTo investigate whether cerebrospinal fluid (CSF) circulation markers alter in patients with probable cerebral amyloid angiopathy (pCAA) and whether they are associated with brain degeneration and cognitive impairment.MethodsWe screened pCAA patients from the ADNI3 database according to the Boston 2.0 Criteria. Fifty-two patients with cognitive impairment (26 pCAA; 26 age-sex-matched non-pCAA) and 26 age-sex-matched cognitively normal control (NC) were included in this study. All participants underwent neurological MRI and cognitive assessments. Choroid plexus (ChP) was segmented using a deep learning-based method and its volume was extracted. Diffusion tensor imaging analysis along the perivascular space (DTI-ALPS) was used to assess perivenous fluid mobility. AD pathological markers (Aβ and tau) were assessed using positron emission tomography. Brain parenchymal damage markers included white matter hyperintensities (WMH) volume and brain atrophy ratio. All markers were compared among the three groups. Correlations among the ChP volume, DTI-ALPS index, parenchymal damage markers, and cognitive scales were analyzed in the pCAA group.ResultsThe three groups exhibited significant differences in cognitive scores, AD biomarkers, and imaging markers. Post hoc analyses showed that patients with pCAA had significantly higher WMH volume, higher Aβ and tau deposition, and lower DTI-ALPS compared to NC. However, no difference in ChPs volume was found among the groups. Controlling for age, sex, and vascular risk factors, partial correlation analyses showed a significant negative correlation between the DTI-ALPS and WMH volume fraction (r = −0.606, p = 0.002). ChP volume was significantly associated with the Montreal cognitive assessment score (r = −0.492, p = 0.028).ConclusionCSF circulation markers were associated with elevated WMH burden and cognitive impairments in probable CAA.